Environmental Factors Influencing Foraging Activity in the Social Wasp Polybia paulista (Hymenoptera: Vespidae: Epiponini) - Naila Cristina de Souza Canevazzi; Fernando Barbosa Noll (Psyche: A Journal of Entomology)
Foraging behavior in social wasps is important in the development of the colony and reflects an important ecological interaction between the colony and the environment. Although the social traits of the colony play a role in the foraging activities, the conditions that establish the space and time limits are mainly physical. Here, we evaluate colonies of Polybia paulista throughout one year in order to verify the foraging activities and the items collected, as well as the importance of temperature, relative humidity, and solar radiation on motivating foraging. Collection of liquids was always higher than that of solids; preys were collected all year long, and nests showed two annual episodic expansions. The linear mixed effects (LME) model used to analyze which weather factors influence the foraging showed temperature as the most influencing factor on the collection of materials.